Panfacial Trauma - A Flexible Surgical Approach - Mall, BB; Kandel, L; Mishra, R; Kandel, S (Journal of Universal College of Medical Sciences, 2014)
Panfacial fractures are those involving the mandible, maxilla, and zygomatic complex at the same time and usually accompanying naso-orbito-ethmoid (NOE) and frontal bone fractures. When there are multiple facial fractures, involving upper & lower face, reconstruction should be approached as puzzle. It is difficult to follow an established pattern of sequencing and organizing the repair of panfacial fractures. Successful reconstructions can be achieved through a flexible approach that adheres to several key principles. The goal of treatment as with all facial fracture is to restore both the functions and pre-injury 3-dimensional facial contours. To achieve this goal, various management schemes have been proposed including “bottom to top,” “top to bottom,” “inside-out,” or “outside-in”. Nevertheless, despite aggressive management, severe post-traumatic deformities continue to appear. The correct timing of surgical intervention and use of rigid fixation allows the restoration of morphological and functional nature of face after Panfacial fractures. The aim of presenting the paper is to analyze the principles that determine the choice of method of treatment and that prevent the development of secondary deformity. DOI: http://dx.doi.org/10.3126/jucms.v2i3.11828 Journal of Universal College of Medical Sciences Vol.2(3) 2014: 41-44